2011
DOI: 10.1093/cvr/cvr221
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of fractalkine on myocardial ischaemia and heart failure

Abstract: FKN promotes myocardial injury and accelerates the progress of heart failure, which is associated with the activation of MAPKs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 30 publications
7
81
3
Order By: Relevance
“…Moreover, the observation of high embryonic mortality and organ defects, including cardiac ventricular septum defects, in CXC chemokine receptor 4 knockout mice indicates a crucial and direct dependence on chemokines in the development and function of the myocardium [81]. Furthermore, we have shown increased CX3C chemokine ligand (CX3CL)1 production in both experimental and clinical HF [82], and very recently, Xuan et al [83] showed that neutralizing CX3CL1 antibody treatment improved HF induced by MI or pressure overload. Other recent studies have also suggested a direct role for chemokines in ECM remodeling.…”
Section: Immunomodulating Therapy Ii: New Therapeutic Targetsmentioning
confidence: 99%
“…Moreover, the observation of high embryonic mortality and organ defects, including cardiac ventricular septum defects, in CXC chemokine receptor 4 knockout mice indicates a crucial and direct dependence on chemokines in the development and function of the myocardium [81]. Furthermore, we have shown increased CX3C chemokine ligand (CX3CL)1 production in both experimental and clinical HF [82], and very recently, Xuan et al [83] showed that neutralizing CX3CL1 antibody treatment improved HF induced by MI or pressure overload. Other recent studies have also suggested a direct role for chemokines in ECM remodeling.…”
Section: Immunomodulating Therapy Ii: New Therapeutic Targetsmentioning
confidence: 99%
“…culture of ventricular cardiomyocytes and fibroblast cells were performed as described elsewhere [30]. Subsequently, primary cardiomyocytes and passage 1 fibroblasts were exposed to histamine, amthamine dihydrobromide (AD, a selective H2R agonist) or famotidine (a selective H2R antagonist -all were purchased from Sigma-Aldrich) for the indicated dose and time as described in the corresponding Figure legend, and then the related gene and protein expression levels, as well as mitochondrial permeability and apoptosis, were analysed.…”
Section: Cell Culturementioning
confidence: 99%
“…10 Moreover, FKN augments myocardial injury and accelerates the progress of heart failure with activation of MAPK/ERK signaling through the G protein-coupled chemokine receptor CX3CR1. 24 The activation of MAPK pathways plays a key role in the progression to cardiac hypertrophy and heart failure. 3 Intriguingly, ings implied regulatory roles of ACE2 in oxidative stress, and the CTGF-FKN-ERK and MMP signaling pathways.…”
Section: Treatment With Rhace2 Suppressed Angii-mediated Oxidative Stmentioning
confidence: 99%